2010
DOI: 10.1071/sh08091
|View full text |Cite
|
Sign up to set email alerts
|

'Show me the money': financial incentives increase chlamydia screening rates among tertiary students: a pilot study

Abstract: Compared with more labour intensive (and therefore more expensive) screening activities conducted over a 6-month period, offering a small financial incentive to tertiary students through text messaging over a 4-day period significantly increased participation in on-campus chlamydia screening. This model could readily be applied to other populations to increase participation in chlamydia screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 18 publications
2
56
0
Order By: Relevance
“…the use of Internet independent of geographic area [28], financial incentives [29], a focus on self-identity [30], and/or the use of social media in combination with role models (people who disclose that they have tested) to overcome low susceptibility and lack of supportive social norms [31]. …”
Section: Discussionmentioning
confidence: 99%
“…the use of Internet independent of geographic area [28], financial incentives [29], a focus on self-identity [30], and/or the use of social media in combination with role models (people who disclose that they have tested) to overcome low susceptibility and lack of supportive social norms [31]. …”
Section: Discussionmentioning
confidence: 99%
“…This increased return rate suggests that the participants’ cash reward was a major contributor to the success of our study. As with other chlamydia screening studies we have undertaken,5 the cash reward appears to have encouraged men to be screened (male to female ratio: 1.7 : 1), although the positivity rate appeared higher among women than men, p=0.04, the 95% confidence limits overlapped (5.3%; 95% CI 2.4% to 8.0% vs 1.4%; 95% CI 0.5% to 3.1%).…”
Section: Discussionmentioning
confidence: 60%
“…Previously explored screening venues include tertiary campuses,5 drug treatment/correctional facilities,6 schools7 and pharmacies 8–10. Community pharmacies have many attributes that make them a logical place to offer chlamydia screening—conveniently located, open long hours, supervised by regulated primary healthcare providers, and no appointments are needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Other studies described incentive programmes, but did not provide a test of the impact of the incentive. 26,31 Of the relevant articles, four considered screening for chlamydia, 25,[32][33][34] three investigated breast or cervical screening, [35][36][37] five investigated tuberculosis (TB) screening or returning to collect test results, [38][39][40][41][42] two investigated work wellness programmes or private health-care plans providing preventative health-care screening, 27,43 and single papers describing incentives in diabetic retinopathy screening, 44 and glycated haemoglobin (HbA 1c ) plus cholesterol screening in patients with diabetes. 45 Three of the four studies investigating chlamydia screening observed a positive impact of incentives, 25,32,34 with evidence that vouchers were more effective than prize draws.…”
Section: Systematic Review Of Literature On Incentives In Screeningmentioning
confidence: 99%